The Influence of Price, Lifestyle and Quality of Service on Purchase Decisions at PT. Astra International, Tbk Gatot Subroto Medan Auto 2000 Branch - Clara Clarissa Nauli; Hendry Hendry; Kevin Kevin; Button Jeksona Siahaan; Riadi Hutapea (Jurnal Mantik, 2020)
The purpose of doing this research is to determine the reduction in purchasing decisions that exist at PT. Astra International, Tbk Gatot Subroto Medan Auto 2000 branch caused by Price, Lifestyle and Quality of Service. The theory to support research is the theory according to experts related to Price, Lifestyle and Quality of Service. 1327 consumers used as population andThe sample in this study amounted to 93 customersout of 30 respondents to do the validity test. The results showed that price, lifestyle and service quality simultaneously and partially had a significant effect on purchasing decisions at PT. Astra International, Tbk, Auto 2000 Gatot Subroto Medan branch with a determination coefficient of 22.6% and the remaining 77.4% is the influence of other independent variables not examined in this study such as financial compensation, etc.